Vibroacoustic Analysis of Cyclic Structures by Using Dof’s Size Reduction and Holographic Measurements - Abdelkhalak El Hami; Dan Borza; José Eduardo Souza de Cursi (Shock and Vibration)
We propose a method for the vibroacoustic analysis of structures having symmetry properties. This method is based on the reduction of the number of the degrees of freedom involved (size reduction) and the use of experimental data (confrontation numerical/experimental). We propose the extension of the method of the linear representations of finite symmetry groups to problems of coupling fluid-structure. This approach, while keeping the quality of the approximations, leads to a significant reduction of the number of degrees of freedom, with a maximal reduction for the so called repetitive structures. Finally, we present a practical case of modal analysis – in air and water – of a ship propeller formed by 3 stainless steel blades. The experimental results are obtained by using the whole-field, non-contact technique of electronic holography.